2015
DOI: 10.4103/2008-322x.176905
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for management of choroidal osteoma without choroidal neovascularization

Abstract: To report a patient with juxtapapillary choroidal osteoma (CO) with serous retinal detachment (SRD) not associated with choroidal neovascularization (CNV) who was successfully treated with a single intravitreal injection of bevacizumab. A 20-year-old woman presented with decreased vision in her right eye. Ultrasonography, fundus autofluorescence, fluorescein angiography (FA) and optical coherence tomography (OCT) were performed. She was diagnosed with juxtapapillary CO with SRD in the absence of CNV. The treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Given its rarity, there is a scarcity of publications regarding treatment options for choroidal osteoma without CNV; focal laser, transpupillary thermotherapy, bevacizumab, and ranibizumab intravitreal injections have all been investigated. [2][3][4][5][6] With regard to antivascular endothelial growth factor (VEGF) therapy, in a retrospective case series of 6 eyes with choroidal osteomaassociated SRF, Song et al [4] reported improved visual and anatomical outcomes following intravitreal injections of bevacizumab; to note, CNV was absent in all but one eye. Clinical response dictated a spectrum of 1, 2, or 3 injections spanning a mean follow up of approximately 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…Given its rarity, there is a scarcity of publications regarding treatment options for choroidal osteoma without CNV; focal laser, transpupillary thermotherapy, bevacizumab, and ranibizumab intravitreal injections have all been investigated. [2][3][4][5][6] With regard to antivascular endothelial growth factor (VEGF) therapy, in a retrospective case series of 6 eyes with choroidal osteomaassociated SRF, Song et al [4] reported improved visual and anatomical outcomes following intravitreal injections of bevacizumab; to note, CNV was absent in all but one eye. Clinical response dictated a spectrum of 1, 2, or 3 injections spanning a mean follow up of approximately 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…The role of anti-VEGF agents in this condition is unclear. However, successful treatment by the use of intravitreal anti-VEGF agents [56,57] or TTT [58] has been reported.…”
Section: Choroidal Osteomamentioning
confidence: 99%
“…However, there are many drawbacks such as limited final visual acuity. Recently, several cases were treated with anti-vascular endothelial growth factor drugs used in age-related macular degeneration or diabetic macular edema such as bevacizumab or ranibizumab [34]. Najafabadi et al [3] reported improvement in a patient treated with intravitreal bevacizumab for choroidal osteoma without CNV.…”
mentioning
confidence: 99%